2008
DOI: 10.1111/j.1551-2916.2008.02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Kinetics and Mechanisms of Hot‐Pressed TiB2–MoSi2Composites

Abstract: The densification of titanium diboride (TiB2) at lower sintering temperature requires the use of sinter‐aid. However, from the high temperature application point of view, it is important to assess whether the presence of sinter‐aid degrades the material properties, including the oxidation resistance. In the present work, the isothermal oxidation behavior of TiB2‐x wt% MoSi2 (x=0, 2.5, and 10) composites was carried out using thermogravimetric analyzer in order to study the effect of MoSi2 content on the oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The oxidation kinetics was slower for the TiB2-10 wt.% MoSi2 due to the presence of SiO2 in the oxide scale. The efficacy of MoSi2 in imparting enhanced oxidation resistance of TiB2 [161]. Murthy et al found a new composite of TiB2 with CrSi2 with excellent oxidation resistance [162].…”
Section: High-temperature Mechanical Propertiesmentioning
confidence: 99%
“…The oxidation kinetics was slower for the TiB2-10 wt.% MoSi2 due to the presence of SiO2 in the oxide scale. The efficacy of MoSi2 in imparting enhanced oxidation resistance of TiB2 [161]. Murthy et al found a new composite of TiB2 with CrSi2 with excellent oxidation resistance [162].…”
Section: High-temperature Mechanical Propertiesmentioning
confidence: 99%
“…10(a). Although the columnar TMO 2 grains are also observed in oxidized bulk diborides [34,97], it is unknown why these grains tend to grow preferentially in one direction. We speculate this columnar growth may be attributed to the restricted TiO 2 grain coarsening in the lateral [100] direction.…”
Section: Tablementioning
confidence: 99%
“…Therefore, non-metallic additives such as carbides (B 4 C [42], SiC [43], TiC [44], TaC [45], WC [46]), nitrides (Si 3 N 4 [9], AlN [10,47], TiN [29,43]), disilicides (TiSi 2 [48], MoSi 2 [7,[49][50][51]) and borides (ZrB 2 [52]) are preferred for applications at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%